The Royal Military Hospital and the War Warehouses of Coimbra: Assistance to injured soldiers and war logistics (1762-1766) - Barbosa, José Luís dos Santos (2017)
This article intends to analyze the Royal Military Hospital and the War Warehouses of Coimbra, two institutions created within the context of the Fantastic War (1762). The investigation is based on the book “Coleçam de todas as despezas”, an unpublished historical source located in the Archive of the University of Coimbra. We intend to analyze the institution’s expenditure, their funding and the personnel, taking into account the political and military context in the 18th century.